Effect of sex ratio and age parent to consumption feed, weight eggs and conversion ration on birds quail (Coturnix coturnix japonica) - Febrianto Lu Hamanay; Muharlien Muharlien; Edhy Sudjarwo (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
Birds quail (Coturnix Coturnix japonica) is a type of bird lots of quail maintained in the community have morphology i.e. small body, round and tail short Setyawn, Sudjarwo, Widodo, and Prayogi (2011) stated that bird quail is one community poultry of the genus Coturnix which can be generated as producer eggs and meat. Destination from study this for knowing the effect of sex ratio and age parent to consumption feed, weight eggs, and conversion feed. Method study is test design Random Complete (RAL) pattern factorial with 2 factors, namely factor 1 is Sex Ratio and factor 2 is age parent with every 3 treatments and 3 replications. Research results show the sex ratio does not give influence real on consumption feed, the weight of eggs, and conversion feed. Average consumption feed of 675.63 (g/ head) to 683.61 (g/ head), average weight egg of 11.28 (g/ item) to 11.60 (g/ item), and the average conversion ration of 5.63 to 6.08. Influence to age parent gives influence that is not real to consumption feed, weight eggs, and conversion feed. Average consumption feed as big as 677.17 (g/ head) to 679.74 (g/ head), average weight egg of 11.28 (g/ item) to 11.55 (g/ item), and the average conversion ration of 5.71 (g/ head ) to 5.92 (g/ head ). Interaction balance male-female and age parent no give influence real to consumption feed, weight eggs, and conversion feed. The conclusion from the research is the influence of the balance of male-female and the age of the parent no give influence the consumption of feed, the weight of eggs, and conversion of feed.